English lingual socio-culture experimental training of high school students - Бронетко, Ірина Анатоліївна (Pedagogy of Higher and Secondary Education, 2015)
Bronetko I. A. English lingual socio-culture experimental training of high school students This article deals with stages of formation of lingual and sociocultural competence of pupils of high school: lingual, situational, integrative creative and corresponding system of exercises with country-studying component.